2019
DOI: 10.1186/s12967-019-2027-8
|View full text |Cite|
|
Sign up to set email alerts
|

A novel role of glutathione S-transferase A3 in inhibiting hepatic stellate cell activation and rat hepatic fibrosis

Abstract: Background and aims Glutathione S -transferase A3 (GSTA3) is known as an antioxidative protease, however, the crucial role of GSTA3 in liver fibrosis remains unclear. As a recently we developed water-soluble pyridone agent with antifibrotic features, fluorofenidone (AKF-PD) can attenuate liver fibrosis, present studies were designed to explore the role of GSTA3 in liver fibrosis and its modulation by AKF-PD in vivo and in vitro. Methods Rats l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…In our twenty-three gene prognosis model, several metabolic genes, including GSTA3, ENTPD2, HK3, CHPT1, CTPS2, and ADCY9, were confirmed for the first time to be correlated with the prognosis of LUAD. GSTA3 is recognized as an antioxidative protease (Chen et al, 2019a). Studies of genetic analysis models and the mechanism of GSTA3 found that it was associated with tumour prognosis (Bruzzoni-Giovanelli et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our twenty-three gene prognosis model, several metabolic genes, including GSTA3, ENTPD2, HK3, CHPT1, CTPS2, and ADCY9, were confirmed for the first time to be correlated with the prognosis of LUAD. GSTA3 is recognized as an antioxidative protease (Chen et al, 2019a). Studies of genetic analysis models and the mechanism of GSTA3 found that it was associated with tumour prognosis (Bruzzoni-Giovanelli et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, GSTA3 was identified and regarded as a prognostic biomarker for nasopharyngeal carcinoma and gastric cancer ( Duan et al, 2018 ; Zhang, Wu & Cheng, 2019 ). GSTA3 inhibits HSC activation and liver fibrosis by inhibiting MAPK and GSK-3 β signalling pathways, suggesting that GSTA3 could be a feasible target for therapeutic interventions for liver fibrosis ( Chen et al, 2019a ). GSTA3 overexpression in breast cancer cells stimulates proliferation and inhibits apoptosis, which leads to chemotherapy resistance and radiation resistance in tumour cells ( Thewes et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Manuscript to be reviewed In our twenty-three gene prognosis model, several metabolic genes, including GSTA3, ENTPD2, HK3, CHPT1, CTPS2, and ADCY9, were confirmed for the first time to be correlated with the prognosis of LUAD. GSTA3 is recognized as an antioxidative protease (Chen et al,2019a). Studies of genetic analysis models and the mechanism of GSTA3 found that it was associated with tumour prognosis (Bruzzoni-Giovanelli et al,2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, GSTA3 was identified and regarded as a prognostic biomarker for nasopharyngeal carcinoma and gastric cancer (Duan et al,2018;Zhang Wu & Cheng,2019). GSTA3 inhibits HSC activation and liver fibrosis by inhibiting MAPK and GSK-3β signalling pathways, suggesting that GSTA3 could be a feasible target for therapeutic interventions for liver fibrosis (Chen et al,2019a). GSTA3 overexpression in breast cancer cells stimulates proliferation and inhibits apoptosis, which leads to chemotherapy resistance and radiation resistance in tumour cells (Thewes et al,2010).…”
Section: Discussionmentioning
confidence: 99%
“…Acetaldehyde stimulates GSK-3β phosphorylation at Ser9 and promotes ROS accumulation, which exacerbates the fibrogenic pathway in human HSC 77 . Glutathione S-transferase A3 (GSTA3) is regarded as an anti-oxidative protease, Chen et al 78 discovered that GSTA3 suppresses intracellular ROS accumulation and further mitigates CCl 4 -induced fibrotic livers in rat models by activating GSK-3β, which results in potently blocked the expression of the α-SMA and FN. Besides, HG stimulates ROS production, leading to the inhibition of GSK-3β and the promotion of EMT process.…”
Section: Relationship Between Gsk-3β and Ros In Fibrosismentioning
confidence: 99%